Students’ motivation and attitude towards the learning of Arabic language: a case study at selected Nigerian universities - Ajape, Kazeem Oluwatoyin; Mamat, Arifin; Sheikh Ahmad, Ismail; Ahmed Mohamed, Ismaiel Hassanein (IIUM Press, 2015)
The study of students’ motivation and attitude in second language (L2) has recently become an important concept across disciplines of second language acquisition (SLA) and communication. This study sought to validate Gadner’s (2009) Attitude Motivation Test Battery (AMBT) on a population of Arabic language learners in Nigeria, and to determine their attitudes and motivations for learning Arabic language. The sample comprised two hundred and eighty eight (288) Arabic language students from six (6) universities in Nigeria. Principal Component Analysis (PCA) was conducted to explore the dimensions of the AMBT in Nigerian context. Twenty three out of the fifty items with factor loading greater than .40 loaded on four factors with eigenvalues greater than 1.0. Four constructs of the questionnaire are: Integrativeness,Attitudes toward the learning situation, Motivation and Instrumentality. The results showed that students had high levels of both integrativeness and attitude towards the learning situation, while their levels of motivation and instrumentality was very low. There was a positive and moderate correlation between integrativenness and attitude toward the learning situation while the correlations between attitude and motivation and integrativeness and motivation were very low. Instrumentality failed to correlate with any of the factors. Multiple regression analysis showed that attitude toward the learning situation was a good predictor of students’ integrativeness. Based on these findings,some pedagogical recommendations were provided for the improvement of the students’ motivation and attitude towards the learning of Arabic language in Nigerian universities.